RANCANGAN STRATEGI PENGEMBANGAN JIWA KEWIRAUSAHAAN MAHASISWA DALAM MEMPERSIAPKAN LULUSAN SIAP KERJA (STUDI KASUS PTAIN DI SUMATERA BARAT) - Harfandi, Harfandi (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2014)
The design strategy in raising of student?s entrepreneurship in The Islamic State College ? PTAIN- in West Sumatera could be conducted by some strategy. The strategies covering: Upgrading the teaching strategy of entrepreneurship curriculum, Increasing the role of college and increasing entrepreneurship?s atmosfire among academic person in college, Mapping the amount of student in each major and faculty, Determining the student in each majors acocording to their talent and their enthusiasm, Having corperation among PTAIN and related institute in entrepreneurship, Creating real synergy between government ?college- real sector, Doing the construction of entrepreneurship by routine, Forming the collegiate forum of the young entrepreneur, Founding the center of business incubation and, Revitalizing the Minangkabau?slocal wisdom.